Multiple Long-Term Conditions, Co-Long-Term Conditions and Polyvascular Disease: Considerations for Evidence Synthesis and Meta-Analyses - Mead, Gillian; Todhunter‐Brown, Alex; Abaraogu, Ukachukwu; Barugh, Amanda; Chauhan, Arohi; Lopez, Juan Erviti; Feigin, Valery; Kshatri, Jaya Singh; Mizuno, Atsushi; Pati, Sanghamitra; Price, Jackie; Providência, Rui; et al. (Wiley, 2025)
Cochrane's scientific strategy for 2025 to 2030 has four research priorities, including improving the lives of people living with multiple chronic conditions. The purpose of this article written by the Cochrane Thematic Group in Heart, Stroke and Circulation is to explore considerations around multiple chronic conditions (also referred to as ‘multiple long‐term conditions’ i.e. two or more long‐term conditions) in systematic reviews. Rather than using the term ‘comorbidity’, we introduce a new term ‘co‐long‐term conditions’. We also explore how to define ‘polyvascular disease’. We suggest that review authors consider co‐long‐term conditions and multiple long‐term conditions in their reviews e.g. extract data about how primary studies address co‐long‐term conditions, perform subgroup analyses according to presence or not of co‐long‐term conditions, and include a section in the discussion about how well participants with co‐long‐term conditions were represented in the primary studies. This is especially pertinent for reviews addressing heart, circulatory or stroke disease, and polyvascular disease.